Marketing mix modeling - Otter, Thomas (Henry Stewart Talks, 2010)
The role of managers, What about standard tools?, Simple example, More realistic example, Simulation study, gains from reallocation, Modeling challenges, Modeling strategy, Estimation strategy, Testing for the supply-side model, Non-informative versus flat priors, Predictive test, Application, Analysis